Taxonomic reassessment of the Selaginella flora of Java, Indonesia - AHMAD DWI SETYAWAN; TATIK CHIKMAWATI; MIFTAHUDIN MIFTAHUDIN; SUTARNO SUTARNO; SUGIYARTO SUGIYARTO; SUNARTO SUNARTO (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Setyawan AD, Chikmawati T, Miftahudin, Sutarno, Sugiyarto, Sunarto. 2026. Taxonomic reassessment of the Selaginella flora of Java, Indonesia. Biodiversitas 27 (2): d270239. https://doi.org/10.13057/biodiv/d270239. Selaginella Beauv. is one of the most taxonomically complex lycophyte genera in tropical Asia, and species delimitation in Java has long been complicated by extensive morphological variation, nomenclatural inconsistency, and contrasting taxonomic interpretations. This study provides a comprehensive floristic and taxonomic reassessment of Selaginella in Java based on 1,962 occurrence records from field surveys and herbarium collections. Species diversity, distribution patterns, and taxonomic relationships were evaluated using comparative morphology, ecological evidence, herbarium examination, and contemporary nomenclatural standardization. A total of 21 species are recognized, including 19 native taxa and two introduced or naturalized species (S. kraussiana and S. uncinata). Updated diagnostic descriptions and identification keys are provided, and several problematic taxa are reassessed. Selaginella ascendens and S. springiana are interpreted within the S. intermedia complex, whereas S. caudata and S. caulescens are treated within the S. plana and S. involvens complexes, respectively. Several vegetative characters traditionally used for species delimitation, including branch flattening, foliage density, and leaf overlap, were found to be highly variable and environmentally responsive, whereas stem pubescence, aristate leaf apices, and certain growth-form characteristics remain more reliable for identification. Floristic comparisons indicate strong affinities between the Javan Selaginella flora and other regions of Sundaland, particularly Sumatra and Peninsular Malaysia, together with secondary connections to Wallacea and the broader tropical and subtropical regions of Asia. The study provides an updated checklist, identification framework, and taxonomic baseline for future ecological, biogeographical, and evolutionary research on Asian Selaginella.